Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4172/2476-2059.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria from Marine Fish: Antimicrobial Resistance and Production of Bacteriocin Effective Against L. monocytogenes In Situ

Abstract: Objective: To determine the antimicrobial resistance of bacteriocin producing marine Lactic acid bacteria and to study the efficacy of bacteriocin against L. monocytogenes during fish preservation.Methods: Lactic acid bacteria from scales and mucus of marine fish viz., Perca sp., Platax sp. and Tuna sp. which showed activity against different spoilage causing bacteria were subjected to antibiotic sensitivity testing. The LAB isolates were also screened for their antagonistic activity against L. monocytogenes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
3
5
0
Order By: Relevance
“…In this study, we demonstrated that the intestinal tracts of two aquatic animals are an important source of probiotic bacteria with bacteriocinogenic potential 38 . These results corroborate the data of Sarika et al 39 , where the authors report that a strain of L. lactis PSY2 isolated from marine perch ( Perca flavescens ) had a bacteriocinogenic profile and a significant antimicrobial effect against several Gram-negative and Gram-positive bacteria, such as L. monocytogenes and S. aureus . The authors also emphasize that such a bacteriocinogenic profile can assist in food preservation; in tests carried out with the strain there was an increase of more than 21 days of shelf-life, useful for the preservation of high-value seafoods.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we demonstrated that the intestinal tracts of two aquatic animals are an important source of probiotic bacteria with bacteriocinogenic potential 38 . These results corroborate the data of Sarika et al 39 , where the authors report that a strain of L. lactis PSY2 isolated from marine perch ( Perca flavescens ) had a bacteriocinogenic profile and a significant antimicrobial effect against several Gram-negative and Gram-positive bacteria, such as L. monocytogenes and S. aureus . The authors also emphasize that such a bacteriocinogenic profile can assist in food preservation; in tests carried out with the strain there was an increase of more than 21 days of shelf-life, useful for the preservation of high-value seafoods.…”
Section: Discussionsupporting
confidence: 91%
“…This could be observed due to the formation of micelles in the medium that stabilized the production of bacteriocin 21 and facilitated the discharge of bacteriocin from the cell surface. 22 However, the effect of Tween 80 greatly depends on the type of bacteriocin and the producing strain. As observed in the present study, Tween 80 used in the half factorial design did not affect BLIS production, which was similarly reported for sakacin A, 23 pediocin A, 24 lactocin S, 25 plantaricin 423 26 and pediocin AcH.…”
Section: Resultsmentioning
confidence: 99%
“…85 This could be brought about by the formation of micelles in the presence of proteins in the medium which stabilized the production of bacteriocin.…”
Section: 80mentioning
confidence: 99%